Oxidative Ammonolysis of Commercial Lignin - a New Concept to Produce N-Modified Lignin - Srivastava, Anita; Bhandari, K. S. (Indian Forester, 2000)
Soda lignin from wheat straw was isolated, purified and subjected to oxidative ammonolysis at 150Â°C, 1.5 Mpa oxygen pressure using 33% ammonia (based on lignin) for 0, 60, 150 minutes with the aim to produce N-modified slow nitrogen releasing fertilizer/soil conditioner. On ammonolysis lignin yielded water soluble and water insoluble fractions. The control and Nmodified lignin samples were analyzed for elemental composition. It was observed that in 60 minutes reaction time 6.83 and 17.24% nitrogen, corresponding to 8.5 and 2.5 C/N ratio could be incorporated in water-insoluble and water-soluble fractions of ammonolysis product and concluded that these products possess acceptable level of nitrogen for its use as slow nitrogen releasing fertilizer/soil conditioner.